AS REPRESENTAÇÕES DE ALUNOS DE UM CURSO DE PEDAGOGIA A DISTÂNCIA SOBRE LINGUAGEM DOCENTE E DIALOGICIDADE - Baffa, Alda Mendes (2016)
This paper conducted an investigation which prioritized the unveiling of representations of students of a pedagogy distance learning course on teaching and dialogical language. This is a qualitative research that conducted a case study involving 17 students from last year (8th semester) of a pedagogy course the distance, a higher education institution, private, located in the Greater ABC region. The guiding research question was: What is the knowledge that the students of the Faculty of Education at a distance have on teaching language, dialogical and its importance for the construction of knowledge? The hypothesis assumes that the studies and training in ODL bring a new type of reflective and operative teaching, but the development and importance attributed to the teaching language come not only from the Faculty of Education in distance education, but also other experiences subjects who are in training. The purpose was to investigate and reflect on the representations of students about the training they are receiving interface with language/dialogicity. To collect data, a questionnaire was applied – with open questions and closed questions – to the profile disclosure and representations about the guiding question of research and analysis of these data was to reference Franco (2003) and Szymanski (2010) for the methodology of content analysis. The theoretical framework that based the research included authors who helped us produce reflections on language, constitution of the subject and the importance of language in the construction of knowledge, as Bakhtin (1999 and 2000), Geraldi (1997) and Orlandi (1997). For the recovery of historical and discussions on the classroom pedagogy course and distance, we selected some authors as Gatti and Barretto (2009); to the crisis of degrees and teaching identity, Gatti and Barretto (2008 and 2010); to research the public policies of training, recovery and encouraging teaching career, Brzenzinski (2013), Tardiff and Lessard (2014), and we seek in Nóvoa (1992) and Libâneo (2002) the professionalism of ideas, professionalization and professionalism; in Saviani (2012) a critical study of the National Curriculum Guidelines for Education Course. In Bahia and Duran (2009) we seek reflections on the training of teachers in distance courses; in Bahia (2014) studies on initial teacher training at a distance, and Azevedo (2013) learning and language in Distance Education. The results of the research point to the great importance given by the students of distance learning to language, their dialogical and interlocutive development, their importance in the construction of knowledge and in the development of the interaction between the interlocutors in Distance Education and the contribution however, as far as dialogue is concerned, the dialogic language is somewhat impaired because the interaction is small (although it exists), and the lack of real-time debates compromises the construction of a dialogue